2006
DOI: 10.1161/01.res.0000237920.70451.ad
|View full text |Cite
|
Sign up to set email alerts
|

Specific Mutations in ABCA1 Have Discrete Effects on ABCA1 Function and Lipid Phenotypes Both In Vivo and In Vitro

Abstract: Abstract-Mutations in ATP-binding cassette transporter A1 (ABCA1) cause Tangier disease and familial hypoalphalipoproteinemia, resulting in low to absent plasma high-density lipoprotein cholesterol levels. However, wide variations in clinical lipid phenotypes are observed in patients with mutations in ABCA1. We hypothesized that the various lipid phenotypes would be the direct result of discrete and differing effects of the mutations on ABCA1 function. To determine whether there is a correlation between the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 29 publications
8
93
0
2
Order By: Relevance
“…The W590S mutation may abolish the coupling of ATP-induced conformational changes of ABCA1 with lipid translocation. The kinetics of apoA-I binding to cells expressing ABCA1-W590S were similar to those of binding to cells expressing wild-type ABCA1, consistent with a previous report showing that the W590S mutation does not impair apoA-I binding (8,(26)(27)(28). Thus, the W590S mutation would not affect the conformational changes of ABCA1 Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The W590S mutation may abolish the coupling of ATP-induced conformational changes of ABCA1 with lipid translocation. The kinetics of apoA-I binding to cells expressing ABCA1-W590S were similar to those of binding to cells expressing wild-type ABCA1, consistent with a previous report showing that the W590S mutation does not impair apoA-I binding (8,(26)(27)(28). Thus, the W590S mutation would not affect the conformational changes of ABCA1 Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The W590S Tangier mutation impairs NaTC-dependent lipid efflux but not apoA-I binding It has been reported that ABCA1 carrying the Tangier disease mutation W590S in the first extra cellular domain is correctly targeted to the plasma membrane and interacts with apoA-I but fails to mediate normal apoA-I-dependent lipid efflux (3,(26)(27)(28). We compared NaTC-dependent lipid efflux from HEK293 cells stably expressing wild-type or ABCA1-W590S fused to GFP at the C terminus.…”
Section: Natc-dependent Lipid Efflux From Wi-38 Cells Mediated By Endmentioning
confidence: 99%
“…Larger sample sizes and partial loss-of-function alleles, respectively. Similar results have been reported previously for another mutation in ABCA1 (p.Trp590Ser) that affects the same amino acid position ( 22 ).…”
Section: Fig 2 Functional Characterization Of Variants In Abca1supporting
confidence: 90%
“…PCR mutagenesis was used to create an ABCA1 mutant library, and mutants were screened for the ability to activate STAT3 and to efflux cholesterol by apoA-I/ABCA1 interaction. For better visualization of ABCA1 expression and sorting, a green fluorescent protein tag was added to the C terminal of ABCA1, and this does not affect ABCA1 function (35)(36)(37).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%